Nanovaccines for malaria using Plasmodium falciparum antigen Pfs25 attached gold nanoparticles. Issue 39 (22nd September 2015) - Kumar, Rajesh; Ray, Paresh C.; Datta, Dibyadyuti; Bansal, Geetha P.; Angov, Evelina; Kumar, Nirbhay
Abstract Malaria transmission-blocking vaccines (TBV) targeting sexual stages of the parasite represent an ideal intervention to reduce the burden of the disease and eventual elimination at the population level in endemic regions. Immune responses against sexual stage antigens impair the development of parasite inside the mosquitoes. Target antigens identified in Plasmodium falciparum include surface proteins Pfs230 and Pfs48/45 in male and female gametocytes and Pfs25 expressed in zygotes and ookinetes. The latter has undergone extensive evaluation in pre-clinical and phase I clinical trials and remains one of the leading target antigens for the development of TBV. Pfs25 has a complex tertiary structure characterized by four EGF-like repeat motifs formed by 11 disulfide bonds, and it has been rather difficult to obtain Pfs25 as a homogenous product in native conformation in any heterologous expression system. Recently, we have reported expression of codon-harmonized recombinant Pfs25 in Escherichia coli (CHrPfs25) and which elicited highly potent malaria transmission-blocking antibodies in mice. In the current study, we investigated CHrPfs25 along with gold nanoparticles of different shapes, size and physicochemical properties as adjuvants for induction of transmission blocking immunity. The results revealed that CHrPfs25 delivered with various gold nanoparticles elicited strong transmission blocking antibodies and suggested that gold nanoparticles based formulations can be developed as nanovaccines to enhance the immunogenicity of vaccine antigens.